Archaeological Investigation and Hazard Assessment Using Magnetic, Ground-Penetrating Radar, and GPS Tools at Dahshour Area, Giza, Egypt - El Emam, A. E.; Lethy, A.; Radwan, Ali M.; Awad, A. (Frontiers in Earth Science, 2021)
An archeological study using magnetic and ground-penetrating radar methods has been performed at the Dahshour region (Giza, Egypt), where various covered structures have not been found because of the long coercion of the zone under the military specialists. Dahshour is the southern extension of the Saqqara and Giza Pyramids plateau, around 25 km south of Cairo. The area is known for its colored pyramids, the white, red, black pyramids, and the famous Bent Pyramid. Four investigation sites were chosen around the Bent pyramid complex. The geophysical investigation has revealed the presence of some buried structures made of mud bricks such as tombs, mud-brick walls, causeway, and remains of an ancient temple. Numerous limestone blocks were also detected. The study indicates the possible existence of an older Valley Temple made of mud bricks and confirms the existence of another causeway that led to the Nile valley. To protect the Egyptian heritage around this vital area, a detailed computation of the current crustal stress/strain state has been performed by taking into account all the available GPS observations. Achieved results indicated that the southern and the southeastern sectors of the investigated area are currently accumulating strain, and this means that there is a possibility to occur future earthquakes around this vital archaeological area. Buried structures are preserved by confinement in the burial materials like a large mold. However, external load or stress can still cause damage. Therefore, during excavation, the stress should be reduced to avoid wall collapsing and structure damage. Therefore, excavation is recommended to start from the stress direction from the southern side.